Magnetic resonance based noninvasive RF nerve stimulator - Ganesh Bharadwaj, C. V. (2013)
A noninvasive method of stimulating the nerve by applying radiofrequency has been presented. The design is based on the concept of magnetic resonance based power transfer. A comparison between electric field on the nerve at the frequency of 450-550 KHz with vacuum placed under a human tissue and the case where it is replaced with a resonant and non-resonant structure was analysed. Calculations were performed by using Ansoft HFSS. Power savings of 7.15% was observed when resonant structures were used, compared to vacuum. Theoretical calculation and simulation of fields were presented.